Behaviour of CRP- Geopolymer Concrete Columns under Axial Loading using ANSYS - Subramani, T.; Piruntha, M. (International Journal of Engineering and Technology, 2018)
Load is one of the big criteria in structural design which took place in the action are static and dynamic. To overcome the requirement of the structural member get designs using geopolymer instead of mild steel which reduce the environmental issues.  In this aspect the geo polymer concrete comes to role i.e., in our examine  to put together the geo polymer concrete the everyday portland cement is absolutely supplemented with fly ash, alkaline liquid are applied for the binding of substances.  Geopolymer concrete is an another  concrete that use fly ash as substitute  material by cement. It shows a new fabric in numerous packages for its use in making of structures. Our project offers to examine the characteristics of geopolymer concrete columns beneath axial loading the usage of ANSYS software.
Keywords: Behaviour; CRP-Geopolymer; Concrete Columns; Axial Loading; ANSYS.